First study to describe a novel HbA2: c.400A > C mutation and Hb Dongguan heterozygote in two unrelated Chinese families - Yao, Cuize; Qin, Danqing; Wang, Jicheng; Bao, Xiuqin; Liang, Jie; Du, Li (Hematology (Luxembourg), 2022)
Here we report two rare α-globin chain variants in two unrelated families: Hb Val de Marne [α133(H16) Ser > Arg (AGC > CGC); HBA2: c.400A > C] and Hb Dongguan [α52(E6) Ser > Cys (TCT > TGT); HBA1: c.158C > G]. Notably, HBA2: c.400A > C is an unreported new variant in the third exon of the α 2 gene, and simple heterozygous unstable Hb Dongguan haematological characteristics are proposed for the first time. Hb analysis was performed by using capillary electrophoresis (CE). Twenty-three common mutations were detected using a suspension array system. Mutations were identified by DNA sequencing. The CE results showed an abnormal peak with incomplete separation from Hb A at zone 8 in two members of Family 1. DNA sequencing confirmed the presence of Hb Val de Marne [α133(H16) Ser > Arg (AGC > CGC); HBA2: c.400A > C]. Five members of Family 2 exhibited an abnormal peak at zone 11, and DNA sequencing confirmed the presence of Hb Dongguan [α52(E6) Ser > Cys (TCT > TGT); HBA1: c.158C > G]. The discovery of HBA2: C.400A > C expands the existing spectrum of α-globin variants. The carriers of simple heterozygous Hb Dongguan generally do not have obvious clinical symptoms. The information in this study will help clinicians understand the screening, molecular diagnosis and clinical significance of Hb variants.